PENGEMBANGAN KAPASITAS KECAMATAN KUTAWARINGIN DALAM PELAKSANAAN PROGRAM PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DIKABUPATEN BANDUNG - Rikki Maulana Yusup; Bambang Agus Diana (Jurnal Administrasi Publik, 2017)
The implementation of the decentralization system in Indonesia at this time has influenced the entire order of Indonesian government from central to regional. the implementation of decentralization system of course has a purpose to realize good governance (Good Governance) As one effort to hold effective local government especially to sub-district, Central Government has set a decision about the implementation of service to society through district Permendagri No. 04 Year 2010 about Guidance Implementation of District Integrated Administration (PATEN) Integrated Service Administration Kecamatan (PATEN) is the implementation of public services in the sub-district from the stage of application to the publication of documents in a sub-district PATEN Program is a long-term project launched by the government for the progress of public service in Indonesia especially in the subdistrict.The purpose to know the form of development undertaken by the Bandung Regency Government in an effort to improve the capacity of the kecamatan in the implementation of the Administration Service Program Integrated Sub-District (PATEN) in Kutawaringin Sub-district, Bandung.